2012
DOI: 10.14723/tmrsj.37.541
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silica Nanofibers Templated by Self-Assembled Peptide Nanostructures

Abstract: There is increasing interest in the synthesis of well-organized silica nanostructures using designed peptides as templates. We have demonstrated an approach to synthesize silica nanofibers by sol-gel condensation of tetramethoxysilane as a silica source on the surface of self-assembled peptide nanofibers. Nonapeptide can undergo self-assembly to form peptide nanofibers and was used as templates for silicification under ambient conditions. Peptide nanofibers were stably entrapped within the silica precipitates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…We previously designed and synthesized a series of amphiphilic β-sheet-forming nonapeptides and showed that they self-assemble to form nanofibers at relatively low peptide concentrations of ∼100 μM in water. The use of water avoids potential metal/salt contamination by buffer solutions. Our results demonstrated that short peptides hold potential for practical applications and encouraged us to employ them as templates to align ZnO nanocrystals along self-assembled peptide nanostructures. Peptides provide significant advantages in structural diversity and manipulation of template molecules compared to small (e.g., amino acids) and large (e.g., proteins) biomolecules.…”
Section: Introductionmentioning
confidence: 87%
“…We previously designed and synthesized a series of amphiphilic β-sheet-forming nonapeptides and showed that they self-assemble to form nanofibers at relatively low peptide concentrations of ∼100 μM in water. The use of water avoids potential metal/salt contamination by buffer solutions. Our results demonstrated that short peptides hold potential for practical applications and encouraged us to employ them as templates to align ZnO nanocrystals along self-assembled peptide nanostructures. Peptides provide significant advantages in structural diversity and manipulation of template molecules compared to small (e.g., amino acids) and large (e.g., proteins) biomolecules.…”
Section: Introductionmentioning
confidence: 87%
“…We also demonstrated the synthesis of silica nanofibers by using a self-assembled nonapeptide nanofiber as a template (RU019: Ac-KIE­ATX­KIE-NH 2 , X = l -2-naphthylalanine) via hydrolysis/condensation of tetramethoxysilane as a silica source at ambient conditions followed by calcination of the peptide–silica hybrids …”
Section: Introductionmentioning
confidence: 99%
“…(1) Small peptides derived from the sequences of isolated proteins for biomineralization or artificial sequences that form nanotubes can be used to precipitate inorganic compounds. [14][15][16][17] In addition, compared with proteins, these peptides are easier to handle;…”
mentioning
confidence: 99%